Associations between physical activity and cardiorespiratory fitness with vascular health phenotypes in older adults: a cross-sectional study - de Sousa, Maria Karolina Ferreira; Silva, Raíssa de Melo; Freire, Yuri Alberto; Souto, Gabriel Costa; Câmara, Marcyo; Cabral, Ludmila Lucena Pereira; Macêdo, Geovani Araújo Dantas; Costa, Eduardo Caldas; Oliveira, Ricardo Santos (Frontiers in Physiology, 2023)
We investigated the associations between physical activity (PA) and cardiorespiratory fitness (CRF) with vascular health phenotypes in community-dwelling older adults. This cross-sectional study included 82 participants (66.8 ± 5.2 years; 81% females). Moderate-to-vigorous physical activity (MVPA) was assessed with accelerometers and CRF was measured using the distance covered in the 6-min walk test (6MWT). The markers of vascular health were: i) arterial function measured as aortic pulse wave velocity (aPWV) estimated using an automatic BP device; ii) arterial structure measured as the common carotid intima-media thickness (cIMT). Using a combination of normal values of cIMT and aPWV four groups of vascular health phenotype were created: normal aPWV and cIMT, abnormal aPWV only, abnormal cIMT only, and abnormal aPWV and cIMT. Multiple linear regression was used to estimate the beta coefficients (β) and their respective 95% confidence intervals (95% CI) adjusting for BMI, and medication for diabetes, lipid, and hypertension, sex, age, and blood pressure. Participants with abnormal aPWV but normal cIMT (β = -53.76; 95%CI= -97.73 – -9.78 m; P = 0.017), and participants with both abnormal aPWV and cIMT (β = -71.89; 95%CI = -125.46 – -18.31 m; P = 0.009) covered less distance in the 6MWT, although adjusting for age, sex and blood pressure decreased the strength of the association with only groups of abnormal aPWV and cIMT covering a lower 6MWT distance compared to participants with both normal aPWV and cIMT (β = -55.68 95%CI = -111.95 – 0.59; P = 0.052). No associations were observed between MVPA and the groups of vascular health phenotypes. In summary, poor CRF but not MVPA is associated with unhealthiest vascular heath phenotype (abnormal aPWV/cIMT) in older adults.